Implementation of Suitcase Lock Security System Using Near Field Communication (NFC) and Global Positioning System (GPS) - Hudiono Hudiono; Galih Muhammad Ichsan; Lis Diana Mustafa (Jurnal Jaringan Telekomunikasi, 2023)
A key is a tool made of metal to open or fasten a door or object that has a lock by inserting it into the hole in the main key. The lock itself is usually used on doors, suitcases, or other objects that require security. The lock on the suitcase itself still has a slight variation and there are still weaknesses, for example the code lock if you forget it cannot be opened, then the padlock and slot lock if the key is lost cannot be opened and can still be broken into by lockpick. The type of research carried out is included in the type of research and development (Research and Development). So, from these problems, a system will be designed and built that can monitor and maximize security automatically so that user's goods are protected from crime or theft by utilizing Near Field Communication (NFC), Global Positioning System (GPS), Magnetic Sensors and Microcontrollers. This system is made portable, so that it can be used in various goods with certain conditions, for example suitcases. The results of this research are portable lock tools, and applications that can integrate lock tools in real time. From the test results obtained accuracy on the gps key, and the security system can run according to the program.